2021
DOI: 10.1101/2021.02.28.21252621
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High failure rate of ChAdOx1 in healthcare workers during Delta variant surge: A case for continued use of masks post-vaccination

Abstract: The Oxford-Astra Zeneca COVID 19 vaccine (AZD1222 or ChAdOx1) is an important part of the global vaccine roll-out against SARS-CoV-2, and a locally manufactured version (Covishield by Serum Institute, Pune, India) is the most commonly used vaccine in India. The vaccination program started in January 2021 and here we report effectiveness of the first dose of Covishield in generating antibody response and its kinetics. We further report differences in the quantitative antibody response amongst individuals who ha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…When the ICS-05/03 spike mutational profile was compared with other spike sequences from the B1 lineages ( Elbe & Buckland-Merrett, 2017 ), they both corresponded to the B.1.617.3 lineage ( Fig 1B ). Notably, the delta variant (B.1.617.2) that dominated the second wave in the country and caused 25.3% of breakthrough infections ( Ujjainiya et al, 2021 Preprint ) shares all spike mutations with B.1.617.3 except T478K ( Fig 1B and C ). The E156G/∆157–158 mutation, first detected on 7 August 2020, subsequently became 35% prevalent worldwide ( Fig 1D ), and by October 2021, it was found in more than 90% of reported sequences from the USA and UK, with a downward trend from India ( Fig 1F ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the ICS-05/03 spike mutational profile was compared with other spike sequences from the B1 lineages ( Elbe & Buckland-Merrett, 2017 ), they both corresponded to the B.1.617.3 lineage ( Fig 1B ). Notably, the delta variant (B.1.617.2) that dominated the second wave in the country and caused 25.3% of breakthrough infections ( Ujjainiya et al, 2021 Preprint ) shares all spike mutations with B.1.617.3 except T478K ( Fig 1B and C ). The E156G/∆157–158 mutation, first detected on 7 August 2020, subsequently became 35% prevalent worldwide ( Fig 1D ), and by October 2021, it was found in more than 90% of reported sequences from the USA and UK, with a downward trend from India ( Fig 1F ).…”
Section: Resultsmentioning
confidence: 99%
“…This emergence of variants coincided with the vaccination drive, prioritized for the frontline workers, older population with subsequent rollouts in high-risk groups, and young adults. While the frontline workers mostly received both doses of ChAdOx1 nCoV-19 (Covishield in India) by March 2021, highly transmissible variants such as delta (B.1.617.2) displayed the ability to cause breakthrough infections ( Ujjainiya et al, 2021 Preprint ). Our surveillance analysis also identified cases that were classified as vaccine breakthrough infections, and it became pertinent to understand the potential of the pathogen targeting vaccinated individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we demonstrated that molecular features of the spike (like L452R and E484Q), already known to confer fitness 7,25,26 , cooperates with alterations in the NTD to enhance spike function further. The now widespread NTD-specific mutation E156G/∆157-158 likely conferred an evolutionary advantage and might underly vaccine breakthroughs found common during the delta outbreaks 5 . One of Delta's siblings, a variant called Lambda that, like Delta, also carries changes in the spike NTD, in addition to L452Q, and these alterations have been linked to the virus' higher infectivity and immune evasion ability 27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…When the ICS-05 spike sequence was aligned with the available spike sequences on GISAID 15 , it corresponded to the B.1.617 lineage, specifically with B.1.617.3 of the delta variant of concern (Figure -1b). Surfaced in the month of March 2021, the delta variant dominated the second wave in the country (Figure -1c) and was reported to have caused 25.3% of breakthrough infections 5 . The E156G/∆157-158 mutation, first detected on 7 th August 2020, subsequently became 35% prevalent worldwide (Figure -1d), and by August 2021, it was found in more than 85% of reported sequences from the USA, UK, and India (Figure -1f).…”
Section: Spike Gene From Breakthrough Infection Harbors a Six-nucleotide Deletionmentioning
confidence: 99%
See 1 more Smart Citation